(untitled) (Revista Electrónica REDINE, 2018)
This qualitative research examined the medical interview (EM) as a benchmark of quality in healthcare organizations, through the phenomenological-hermeneutic, ethnographic method paradigm and harvesting techniques: participant observation, focus groups with medical residents medical internal (RMI), targeted RMI testimonials written by patients and open interviews. Techniques of data analysis are grounded theory through the constant comparative method (MCC) and triangulation techniques. Developed in three phases: I grasp the object of study epistemologically. II field research and information recorded: and III data analysis and theorizing. It was found that MS is communication that is instrumental to the health care organization to serve users with human qualities, making medical history, diagnosis and treatment to the patient, as an act of change, organizational transformation, professional, personal, human, and benchmark of hospital care. Keywords: medical interview, health organization, quality, ethnography.